Imaging of cervicothoracic junction anatomical variation in neurogenic thoracic outlet syndrome: A scoping review protocol - Hugo O.H. Beaumont; George Slade; Hazel Brown; Tom J. Quick (PLoS ONE, 2026)
Objective The objective of this scoping review is to systematically map the extent and nature of the literature on the use of imaging for assessing cervicothoracic junction anatomical variation in patients with neurogenic thoracic outlet syndrome. Introduction Neurogenic thoracic outlet syndrome is a complex, disputed diagnosis that lacks a definitive gold-standard test, despite being the most common thoracic outlet syndrome subtype. Imaging is essential for identifying anatomical variations, such as cervical ribs, and excluding competing diagnoses. This review aims to clarify how imaging modalities are utilized to describe, classify, and assess these anatomical variations, and how these findings are explicitly linked to diagnosis or management. Selection criteria This review will consider studies that include patients with neurogenic thoracic outlet syndrome and evaluate the role of imaging in assessing anatomical variations at the cervicothoracic junction. All study designs, including reviews, quantitative, and descriptive studies, will be considered. This review will exclude studies where the primary focus is the diagnosis of arterial or venous thoracic outlet syndrome using vascular imaging modalities. Methods The search strategy will employ a three-step process, developed in consultation with a medical librarian, utilizing a final comprehensive search across multiple major databases (e.g., MEDLINE, CINAHL, Embase, Scopus) and gray literature sources. Studies published in the English language and from database inception will be included. Following screening by two independent reviewers, data will be extracted, synthesized descriptively, and presented in tabular and narrative format to map the identified evidence. Review Registration Open Science Framework https://osf.io/hybg2